Faktor-faktor motivasi belajar eksternal yang mempengaruhi hasil belajar Menggambar teknik I - Viki Fauzi (LPPM Universitas Negeri Jakarta, 2015)
This study aims to find out about the factors that affect external motivation to learn the results of Drawing Techniques I learned in college students S1 Studies Program of Technical Education Building, State University of Jakarta. Place of this research was conducted at the Department of Civil Engineering, State University of Jakarta in October-December 2011.In this study using survey method. The population in this study were students of S1 Studies Program of Technical Education Building Department of Civil Engineering Faculty of Engineering, State University of Jakarta of 2007, 2008, 2009, and 2010 as many as 262 students and a sample of 72 students who are determined using the calculation Yamane with sampling techniques using simple random sampling . The instrument used was a questionnaire for data capture factors external motivation to learn and value the learning outcomes data UAS for Engineering Drawing I. Reliability of the results obtained from the calculation of r values for the factors of external motivation to learn at 0.935.Based on the research results can be concluded that there are factors that influence motivation to learn external learning outcomes Mechanical Drawing I. In sub-indicators to obtain a family concern that is the largest average value 3.78, and the lowest mean value contained in the sub-indicators campus environment that is equal to 2.95. Overall indicator of family environment to obtain a mean value of 3.51, an indicator of the campus environment to obtain a mean value of 3.32, and for community environmental indicators obtained average value of 3.48.Based on research results obtained that the family environment is a factor external motivation to learn the most dominant in affecting learning outcomes of Engineering Drawing I with a mean value of 3.78.